2000
DOI: 10.1002/1098-1004(200007)16:1<90::aid-humu20>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Three different premature stop codons lead to skipping of exon 7 in neurofibromatosis type I patients

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder affecting one in 3,500 individuals. The mutation rate in the NF1 gene is one of the highest known for human genes. Compared to other methods, the protein truncation test (PTT) provides improved efficiency in detecting NF1 mutations which are dispersed throughout the gene which spans 350 kilobases of genomic DNA. We have applied the PTT and subsequent sequence analysis of cloned cDNA to identify mutations in NF1 patients. We report here th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
3
8
0
1
Order By: Relevance
“…The same has been shown in another study of exon 7 skipping in which the RNA structure overall was not affected by mutations, suggesting that the skipping of exon 7 can be easily induced or that the mutations disrupt exon enhancer sites as an alternative mechanism (Wimmer et al 2000a). Wimmer et al (2000a) have also found 11 different RT-PCR aberrations within exons 1-10a by using aged blood of a normal individual, showing that this can mimic results from alterations of exon splicing caused by mutations in NF1 patients (Wimmer et al 2000b). However, other than the exon 7 observation, we have not clearly detected any of their other reported abnormalities suggesting that laboratory-specific methods and factors may also play a role in the precision of these results.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The same has been shown in another study of exon 7 skipping in which the RNA structure overall was not affected by mutations, suggesting that the skipping of exon 7 can be easily induced or that the mutations disrupt exon enhancer sites as an alternative mechanism (Wimmer et al 2000a). Wimmer et al (2000a) have also found 11 different RT-PCR aberrations within exons 1-10a by using aged blood of a normal individual, showing that this can mimic results from alterations of exon splicing caused by mutations in NF1 patients (Wimmer et al 2000b). However, other than the exon 7 observation, we have not clearly detected any of their other reported abnormalities suggesting that laboratory-specific methods and factors may also play a role in the precision of these results.…”
Section: Discussionsupporting
confidence: 68%
“…Stress conditions, such as cold shock, could lead to alterations in the secondary structure of RNA in certain regions of the molecule and might be responsible for the exon skipping in aged blood samples. The same has been shown in another study of exon 7 skipping in which the RNA structure overall was not affected by mutations, suggesting that the skipping of exon 7 can be easily induced or that the mutations disrupt exon enhancer sites as an alternative mechanism (Wimmer et al 2000a). Wimmer et al (2000a) have also found 11 different RT-PCR aberrations within exons 1-10a by using aged blood of a normal individual, showing that this can mimic results from alterations of exon splicing caused by mutations in NF1 patients (Wimmer et al 2000b).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A total of 124 (44%) mutations of various types affected splicing (173/374 patients). We and others have shown that several of these mutations generate a NF1-transcriptional profile rather than a single mutated mRNA, where correctly spliced mRNAs containing the original DNA mutation coexist with mRNAs exhibiting a splicing alteration (Messiaen et al, 2000;Wimmer et al, 2000b;Zatkova et al, 2004;Pros et al, 2006). For example, we have already shown that mutations c.910C>T, c.5546G>A, c.6791dupA and c.6792C>A generate different proportions of mutated transcripts for each NF1 mutation (Pros et al, 2006) and that these proportions were similar among patients with the same mutations.…”
Section: Resultsmentioning
confidence: 81%
“…For this reason, although in silico predictions represent an invaluable tool for the researcher in this field, special care should be exercised when predicted premRNA structures are correlated with splicing behavior. As an example, in silico studies of NF-1 gene transcripts (50,58), which are implicated in the generation of human tumors, have been challenged by successive reports (99,106). In fact, these studies have shown that the analyses reporting correlations between in silico predicted changes in secondary structure and splicing in these systems are heavily dependent on the RNA window taken into consideration, making it very difficult to assign significance to the suggested correlations.…”
Section: Can Alterations In Pre-mrna Secondary Structure Be Involved mentioning
confidence: 99%